Evaluating the computerized exams at the University of Applied Sciences in Gaza from the faculty members’ point of view - Matter, Yousef Khalil; Al-Qarnawy, Loay Ibrahim (Journal of Educational and Psychological Sciences, 2021)
The average overall evaluation of the computerized exams was 3.53 (qualitatively described as high). On the basis of the three domains; the evaluation of the attitudes of the academics towards the computerized exams was the highest (3.66) which was qualitatively described as high, the evaluation of the development techniques of the computerized exams from UCAS academics’ point of view was evaluated as the second (3.58) and was qualitatively described as high, and the evaluation of UCAS technical and humanitarian capabilities was the lowest (3.35) and was evaluated as medium.For the sake of development of the computerized exams at UCAS and the Arabian and Palestinian Universities, the researchers recommend to attract and employ external experiences and competencies to enhance the academic’s skills to improve computerized tests, conduct a semi-permanent meeting for academic prior to exams to refine their skills when dealing with any modern technologies that enhance holding the computerized exams, and conducting quarterly lectures for students within an Introduction to Computer course to upgrade their skills and facilitate dealing with computerized exams.
Keywords: evaluation; Computerized tests; Gaza College of Applied Sciences; education institution